2010
DOI: 10.1159/000313492
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Accumulation of Lanthanum as Compared to Aluminum in Rats with Chronic Renal Failure – Possible Harmful Effects after Long-Term Exposure

Abstract: Background: Lanthanum (La) carbonate is a new treatment for hyperphosphatemia. We tested the effects of oral La carbonate and aluminum hydroxide, respectively, on tissue accumulation and liver function in rats with chronic renal failure (CRF). Methods: Adult male non-CRF and CRF rats were randomly assigned to 3 groups receiving either standard diet (St.D), or the same diet supplemented with 3% La carbonate (non-CRF La vs. CRF La) or 3% aluminum hydroxide (non-CRF Al vs. CRF Al). Results: After 12 weeks, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
(49 reference statements)
1
11
1
Order By: Relevance
“…It has been observed that the decrease in body and liver weights and the lowered liver function were caused by lanthanum administration in rats with experimental chronic renal failure [10,11]; however, in the present study using normal rats, these adverse effects were not observed. This indicates that there is a difference in the effect of lanthanum administration between normal rats and rats with experimental renal failure; toxicity of lanthanum is very low, at least in normal rats.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…It has been observed that the decrease in body and liver weights and the lowered liver function were caused by lanthanum administration in rats with experimental chronic renal failure [10,11]; however, in the present study using normal rats, these adverse effects were not observed. This indicates that there is a difference in the effect of lanthanum administration between normal rats and rats with experimental renal failure; toxicity of lanthanum is very low, at least in normal rats.…”
Section: Discussioncontrasting
confidence: 85%
“…Although serious adverse side effects have not been observed in any human cases of long-term lanthanum administration [9], some researchers have pointed out the adverse effects of lanthanum and the harmfulness of long-term lanthanum administration mainly based on animal experiments; lanthanum decreased liver function [10,11]. Generally, adverse effects induced by chemical substances may occur more readily in animals fed semipurified diets than those fed commercial conventional diets composed of natural products containing several phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanum carbonate has significant P‐binding properties and good efficacy 8 . Preclinical data reported decrease in liver (and total body) weight and mild alterations in liver function; 9 however, this has not been reported in humans (up to 6 years of treatment) 10…”
mentioning
confidence: 93%
“…7 Lanthanum carbonate has significant P-binding properties and good efficacy. 8 Preclinical data reported decrease in liver (and total body) weight and mild alterations in liver function; 9 however, this has not been reported in humans (up to 6 years of treatment). 10 The limitations of available OPB outline the need for Ca-free agents that can safely and effectively reduce serum P to target concentrations.…”
mentioning
confidence: 99%
“…Their cells can store significant amounts of metal ions without any damage to the organism (Linder 2001). In extreme cases excessive intake of elements leads to cell and organ damage and disruption of their functions (Evans and Abraham 1973;Amiard-Triqut et al 1986;Nikolov et al 2010).…”
Section: Introductionmentioning
confidence: 99%